2015
DOI: 10.1007/s00508-015-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient smoking cessation therapy: truth or dare?

Abstract: Successful quitters fail to report of an unbearable strong desire to smoke. Such unfounded fear should be communicated. Weight gain remains an undesired side effect. Hence, it is crucial to diagnose individuals more prone to weight gain and offer coping strategies thus reducing the risk of developing obesity. Nevertheless, the outcome of the study should be an encouragement to also heavy smokers and empower them to undertake smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Withdrawal symptoms often start quickly and reach their peak intensity within 24–28 hours of quitting 9 . The duration of the residential treatments that were reviewed varied from 3 days to 3 weeks and included common elements such as counseling, personalized medication, and complementary therapies such as relaxation and stress management 18,23,24 . Currently, there are no available data on the most effective duration of a residential stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Withdrawal symptoms often start quickly and reach their peak intensity within 24–28 hours of quitting 9 . The duration of the residential treatments that were reviewed varied from 3 days to 3 weeks and included common elements such as counseling, personalized medication, and complementary therapies such as relaxation and stress management 18,23,24 . Currently, there are no available data on the most effective duration of a residential stay.…”
Section: Discussionmentioning
confidence: 99%
“…9 The duration of the residential treatments that were reviewed varied from 3 days to 3 weeks and included common elements such as counseling, personalized medication, and complementary therapies such as relaxation and stress management. 18,23,24 Currently, there are no available data on the most effective duration of a residential stay. Besides effectiveness, in practice, the financial costs and necessary investments are likely factors to consider when designing the optimal duration of residential stay.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that heavy smokers or those smoking for decades sometimes showed substantial anticipatory uncertainty about their ability to not smoke for 26 hours. The literature has reported anticipatory and psychological reactions to cessation and, for some smokers, increased negative affect even before cessation 41 , and unfounded fears about having a strong desire to smoke after cessation have been described in non-psychiatric samples 42 . • All subjects in our sample received psychiatric treatment including pharmacotherapy, which may have blunted the increase in withdrawal symptoms during smoking abstinence.…”
Section: Discussionmentioning
confidence: 99%